Analisis Perencanaan Laba yang Diharapkan Menggunakan Analisis CVP - Rusadi, Lia Atthahira; Somad, Tiara Risonia; Ratih Kusumastuti (CV. Kalimasada Group, 2023)
Cost volume profit analysis (cost volume profit) is a tool in planning the profit expected by the company by connecting the links between costs, volumes, and profits of a company. While profit planning is to determine what actions the company's management will take during a certain period of time in relation to the profit target to be achieved by the company. The purpose of this research is to describe the results of the cost volume profit analysis in profit planning which is expected to use cost volume profit analysis. This research was conducted at PT. Unilever Indonesia Tbk. which have been listed on the IDX. The method used in this research is descriptive method. While the analysis used in this study is quantitative analysis in which there is a calculation of cost volume profit analysis and profit planning. This profit volume cost analysis will be analyzed using break even point analysis, margin of safety, operating leverage and profit target planning analysis. The data used comes from the 2019- 2021 profit and loss financial statements belonging to PT Unilever Indonesia Tbk. Companies that have many product variants such as PT Unilever Indonesia Tbk are suitable to use cost- volume profit analysis as the basis for planning corporate profits. The results of the study generally show that the company is able to exceed the expected profit target and exceed the break-even point, even though the value and ratio of the margin of safety decreased successively from 2019 to 2021.